Analysis of time designated for mathematics studies in Lithuania between two world wars - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2021)
Analysis of time which is designated for mathematics studies in Lithuania between two world wars is presented in this article. The history of education is described. Comparisions between European countries (France, Austria, Germany) and Lithuania of this period are presented in this article.
Keywords: results of analysis time which is designed to mathematics study; history education in Lithuania between two word wars; comparision time which is designed to mathematics studies